Autonóm repülő robotok alkalmazása vízelvezető csatornák felügyeletére (Using Autonomous Flying Robots to Monitor Canals) - Anita Szabó (DETUROPE)
The weather change of the recent decades caused changes that can be felt in Vojvodina, too. In this economy which mostly relies on agriculture, farmlands are afflicted with floods one year and drought in another. To balance these, canal systems are already built. Because of the size of the canal network, its periodic monitoring requires huge amount of work and recourses. Our research investigates possibility of aerial monitoring of regional irrigation and drainage canals using drones. Autonomous flying robots are becoming more and more popular in recent years. This is happening because the technology they are based on is getting less expensive, quadcopters have broken into the consumer market, so the manufacturing costs are constantly decreasing. This enables them to be used both in research and in the industry without having to pay huge amounts of money. In this research, a commercially available quadcopter has been used to monitor water canals around the city. By design, the device has a built-in camera and wireless internet capabilities. These allow to take photos, record video and upload them to the controlling device. It is also possible to stream the live video to the device in real time. The controlling device can be a personal computer, a tablet or even a mobile phone. It is planned that the client software be extended with capability to upload video and photos to the cloud for later reference. Also, other sensors can be added to the device, too.